Diagnosis and risk factors of injuries in wheelchair fencing parathletes during a national championship - da Silva Neto, C. A. F.; da Cunha, E. K. C.; e Silva, M. P. M. (Brazilian Journal of Physical Therapy, 2025)
Background Wheelchair fencing is a sport for para-athletes with physical disabilities. To minimize the impacts of disability, para-athletes are divided into three functional categories: A (highest functionality), B and C (lowest functionality). The sport emerged as a rehabilitation process but has evolved into a high-performance sport. With this evolution, para-athletes have begun to face a greater training load, which can increase the incidence of injuries. In this context, accurate identification of diagnoses and analysis of risk factors are essential for the implementation of preventive strategies.